Assessment of Human Resource and Material Cost Proportions in Building Construction Projects - Niapele , Idrus; Muhammad, Amiruddin; Faruk, Fitriyanti (SCIENTIA: Journal of Multi Disciplinary Science, 2025)
This study examines the proportional distribution of human resource (HR) and material costs in building construction projects, using the Rectorate Building construction at Nurul Hasan University as a case study. Efficient cost allocation is a critical component of construction project management, as imbalances between labor and material expenditures can lead to budget overruns, schedule delays, and compromised quality. Employing a quantitative descriptive approach, this research analyzes official project documents, including the Bill of Quantities (BoQ) and standardized unit price analyses, to determine the relative contributions of HR and material costs across major work categories. The findings indicate that material expenditures significantly dominate project spending, accounting for 80% of the total direct cost, while HR costs represent only 20%. Work categories such as reinforced concrete, masonry, roofing, and carpentry demonstrate strong material dependency due to the high cost of construction materials such as steel, cement, aggregates, timber, and prefabricated components. In contrast, preparatory and early-stage works show a higher proportion of labor costs, reflecting their reliance on manual activities. The study also evaluates indirect costs and contractor profit margins, revealing that non-resource expenditures constitute 10% of the total project value, and the contractor’s profit margin stands at 9.1%, both of which fall within acceptable industry standards. These results highlight that while material management plays a decisive role in cost efficiency, effective labor allocation and supervision remain essential for ensuring construction quality. Overall, the research offers valuable insights for practitioners seeking to improve cost control strategies in medium-scale building construction projects.